Stakeholder Analysis for Adopting a Personal Health Record Standard in Korea. Issue 2 (June 2015) - Kang, Min-Jeoung; Jung, Chai Young; Kim, Soyoun; Boo, Yookyung; Lee, Yuri; Kim, Sundo; Choi, Yeonmi; Lee, Eui-Kyung; Kim, Sukil
Background: Interest in health information exchanges (HIEs) is increasing. Several countries have adopted core health data standards with appropriate strategies. Objective: This study was conducted to determine the feasibility of a continuity of care record (CCR) as the standard for an electronic version of the official transfer note and the HIE in Korean healthcare. Method: A technical review of the CCR standard and analysis of stakeholders' views were undertaken. Transfer notes were reviewed and matched with CCR standard categories. The standard for the Korean coding system was selected. Stakeholder analysis included an online survey of members of the Korean Society of Medical Informatics, a public hearing to derive opinions of consumers, doctors, vendors, academic societies and policy makers about the policy process, and a focus group meeting with EMR vendors to determine which HIE objects were technically applicable. Results: Data objects in the official transfer note form matched CCR standards. Korean Classification of Diseases, Korean Standard Terminology of Medicine, Electronic Data Interchange code (EDI code), Logical Observation Identifiers Names and Codes, and Korean drug codes (KD code) were recommended as the Korean coding standard. 'Social history', 'payers', and 'encounters' were mostly marked as optional or unnecessary sections, and 'allergies', 'alerts', 'medication list', 'problems/diagnoses', 'results', and 'procedures' as mandatory. Unlike the US, 'social history' was considered optional and 'advance directives' mandatory. At the public hearing there was some objection from the Korean Medical Association to the HIE on legal grounds in terms of intellectual property and patients' personal information. Other groups showed positive or neutral responses. Focus group members divided CCR data objects into three phases based on predicted adoption time in CCR: (i) immediate adoption; (ii) short-term adoption ('alerts', 'family history'); and (iii) long-term adoption ('results', 'advanced directives', 'functional status', 'medical equipment', 'vital signs', 'plan of care', 'social history'). Conclusion: There were no technical problems in generating the CCR standard document from EMRs. Matters of concern that arose from study results should be resolved with time and consultation.